Negotiated Management as a Tool to Achieve Social Control over Political Protest and Social Movement Organizations - Lynn, Tamara J. (Advances in Social Sciences Research Journal, 2022)
Social movement scholars describe negotiated management as a process of collaboration between those in power and those in resistance. For this research, content analysis and critical discourse analysis are used to evaluate questionnaire responses from law enforcement agencies in communities where competing grassroots political organizations engaged in political protest. Findings indicate that law enforcement exercise different levels of social control toward those least likely to engage in, or submit to, a negotiated management model of policing. I argue that responses toward organizations, as reported in questionnaire responses, demonstrates a structural permanence of social control. Negotiated management between the state and competing grassroots political organizations is a tool used to achieve informal control. Organizations that fail – or choose not – to engage in informal social control of their members risk escalated force by police agencies that seek compliance. Results of this research increase understanding of law enforcement responses to political protest groups.